Comparative analysis of maize based livelihoods in drought prone regions of eastern Africa: adaptation lessons for climate change - Erenstein, Olaf; Kassie, Girma T.; Mwangi W (2011)
There is an increasing recognition of climate change, and that it is likely to result, inter alia, in more erratic rainfall that will affect Africa’s predominantly rainfed agriculture. Much of Africa’s current rainfed agriculture is already variously exposed to weather vagaries such as dry spells and drought and farmers in such areas have developed an array of livelihood strategies and management practices to cope with drought risk. These instances provide a fertile learning ground to assess potential adaptation options and their implications. The paper draws from parallel household surveys in drought prone maize growing areas in Ethiopia, Kenya, Uganda and Tanzania to illustrate how resource poor farmers are already coping with drought. The parallel surveys used a similar approach and questionnaire that allow for contrasts of a number of indicators – particularly in terms of household assets, livelihood strategies and crop management practices. These illustrate how farmers in a similar agro-ecological environment but with different socio-economic and institutional settings have variously adapted to living with drought and how the inherent weather risk co-determines the livelihood portfolio, agricultural intensification incentives and system development pathways. This helps in identifying the challenges and opportunities for agricultural intensification and to draw out some policy implications and lessons for agriculture’s adaptation to climate change.